War In Fiqh Review And Humanitarian Law - Hasanuddin, Hasanuddin (International Journal of Education, Vocational and Social Science, 2023)
The main problem in this research is how to review war in fiqh and humanitarian law, how to determine the reasons for the permissibility of war in jurisprudence and humanitarian law, and how to post-war rehabilitation and reconstruction. This type of research uses descriptive qualitative and normative research. This research is a literature study. Sources of data come from legal materials that are primary, secondary and tertiary. The approach used is historical, normative theological and juridical approaches. Processing of legal materials using data analysis techniques with critical analysis. This study concludes that war in the view of fiqh is jihad fi sabilillah. However, the term jihad does not represent all forms of warfare in Islam. The principle of war in fiqh is an attempt to uphold dienul haq by risking wealth and life. Enforcement is intended to be carried out against disbelievers who hinder and make enemies of their adherents. The principle of fiqh sets limits (ethics) in war by not exceeding the limit. In humanitarian law there is the principle of military necessity, the principle of chivalry and the principle of humanity. The reason for war in fiqh is because it eliminates barbarity and tyranny, not because it is for imperialism. Another reason is because of self-defense or defending the homeland of the Muslims, or preventing from the dangers and threats of the infidels. In humanitarian law there is no provision for reasons of war. However, humanitarian law does not prohibit fighting. It only regulates hospitality which includes provisions for the use of means and methods of war, as well as protection for victims of war. Post-war reconstruction and rehabilitation were realized when the war ended through an absence of war (peaceful) phase. This phase is indicated by the end of the war.